2019
DOI: 10.21203/rs.2.9987/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Larva of greater wax moth Galleria mellonella is a suitable alternative host for the fish pathogen Francisella noatunensis subsp. orientalis

Abstract: Background: Francisella noatunensis subsp. orientalis (Fno) is the etiological agent of francisellosis in cultured warm water fish, such as tilapia. Antibiotics are administered to treat the disease but a better understanding of Fno infection biology will inform improved treatment and prevention measures. However, studies with native hosts are costly and considerable benefits would derive from access to a practical alternative host. Here, larvae of Galleria mellonella were assessed for suitability to study Fno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently, a study on the suitability of Galleria mellonella larva as an infection model for piscine francisellosis showed that early tetracycline treatment increases larval survival when infected with fish‐isolated F. orientalis (previously Francisella noatunensis subsp. orientalis ) (Djainal et al, 2020). However, the effectiveness of different OTC dosages at different stages of F. orientalis infection, and their effects on tilapia tissues, is poorly addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study on the suitability of Galleria mellonella larva as an infection model for piscine francisellosis showed that early tetracycline treatment increases larval survival when infected with fish‐isolated F. orientalis (previously Francisella noatunensis subsp. orientalis ) (Djainal et al, 2020). However, the effectiveness of different OTC dosages at different stages of F. orientalis infection, and their effects on tilapia tissues, is poorly addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%